New Evidence for Upland Occupation in the Mesolithic of Scotland. (16th December 2020) - Wickham-Jones, C.R.; Noble, G.; Fraser, S.M.; Warren, G.; Tipping, R.; Paterson, D.; Mitchell, W.; Hamilton, D.; Clarke, A.
Abstract : This paper discusses the evidence for periodic human activity in the Cairngorm Mountains of Scotland from the late 9th millennium to the early 4th millennium cal bc . While contemporary paradigms for Mesolithic Europe acknowledge the significance of upland environments, the archaeological record for these areas is not yet as robust as that for the lowland zone. Results of excavation at Chest of Dee, along the headwaters of the River Dee, are set into a wider context with previously published excavations in the area. A variety of site types evidences a sophisticated relationship between people and a dynamic landscape through a period of changing climate. Archaeological benefits of the project include the ability to examine novel aspects of the archaeology leading to a more comprehensive understanding of Mesolithic lifeways. It also offers important lessons in site survival, archaeological investigation, and the management of the upland zone.